AKTIVITAS CKMB DAN MASA CKMB TERKAIT KARDIAK TROPONIN-I DALAM GEJALA KORONER AKUT - Tonang Dwi Ardyanto; Tahono Tahono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Coronary Heart Disease (CHD) is the leading cause of death recently, including in Indonesia which is raised to 25%. Acute Coronary Syndrome (ACS) is its common clinical manifestation. Therefore, the necessity for a sensitive as well as specific diagnostic biomarker for ACS should be addressed in discriminating the ACS patient and its related risks. The diagnostic sensitivity of characteristic electrocardiography pattern in ACS cases were reported to be variatively between 55–75%. In laboratory diagnostic, ACS markers among others are CKMB activity, CKMB mass as well as Cardiac Troponin-T and Troponin-I (cTnT and cTnI). Currently, cTnI is the gold standard. The present study is to know the analysing of the CKMB activity as well as the mass diagnostic performance in the detectionof ACS in the patient presenting with chest-pain at RSDM, by using cTnI as the standard of reference. As many 30 samples, 18−65 years old, were selected trough incidental sampling method from the subjects presenting with chest-pain no longer than 6 hrs before admission. The blood samples were drawn at admission and 6 hrs afterward. The CKMB activity (immunoinhibition assay), CKMB mass (ELFA) and cTnI (ELFA) measurement were performed on each sample. The analysis showed that cTnI cut-off on 0.1 μg/L (ESC/ACC 2000) was most optimal in the laboratory diagnostic of ACS compared to that of 0.01 μg/L (ESC/ACC 2007 update) and 1.0 μg/L (WHO). Using the cTnI cut-off on 0.1 μg/L, on admission (0 hr) the diagnostic efficiency of CKMB mass was 56.7% while that of CKMB activity was 60.0%. While on the serial measurement (6 hrs), the diagnostic efficiency of CKMB mass was 76.6% while that of CKMB activity was 56.7%. The results showed that by serial measurements, CKMB mass is superior than CKMB activity in the diagnosis of ACS in patient presenting with chest-pain. Further researches are necessary to elaborate the comparison elucidatively. The results of the study considered that in designing the protocol for laboratory examination should carried out in patient presenting with chest pain.